Diálogos interdisciplinarios sobre las relaciones de poder que hay entre los tecnocratas del Proyecto de navegabilidad del río Meta y los achaguas. - ARDILA LUNA, Diana Carolina; PRADA RODRÍGUEZ, Manuel Leonardo (Humanidades: Revista de la Universidad de Montevideo, 2023)
The article analyzes the relationship between the technocrats of the River Meta Navigability Project and the Achagua indigenous community in Colombia. The importance of the Achagua's participation in co-directing the project to ensure the survival of the river and future generations is highlighted. The article examines the impact of neoliberal techniques on the daily life of the Achagua people and how it seeks to impose itself as the only valid way of proceeding. Other anthropological studies that explore the meaning of rivers for different societies are also mentioned.